The first sexually dimorphic species of Oribatella (Acari, Oribatida, Oribatellidae) and a review of sexual dimorphism in the Brachypylina - Behan-Pelletier, Valerie M.; Eamer, Barbara (Zootaxa, 2010)
The oribatid mite genus Oribatella includes over 100 named species, none of which shows distinct sexual dimorphism in the octotaxic system of dermal glands. We propose a new species of this genus, Oribatella canadensis sp, nov., collected from dry soil habitats in western Canada, that shows distinct dimorphism in these dermal glands, the first record of this dimorphism in the Oribatelloidea. The posterior pair of glands in males, but not females, is enlarged and associated with a shallow, medial pit-tubercle complex, and is generally similar to convergent dimorphisms in some genera of Mochlozetidae (Oripodoidea), Mycobatidae (Ceratozetoidea) and Galumnidae (Galumnoidea). We describe this species based on adult and nymphal stages, and expand the diagnosis of the genus to accommodate the newly described immatures. We review the expression of sexual dimorphism in brachypyline oribatid mites and discuss its association with periodically dry habitats.